The characterization of the stress fields near a crack tip for a compact specimen for elastic-plastic materials dominated by the plane strain state - Iwanowska-Chomiak, Beata; Walicka, Anna (Zielona Góra: Uniwersytet Zielonogórski)
Interstitial space, also called interstitum, separating the vital organs of a human body, is the primary source of lymph and is a major fluid compartment in the body.Interstitial space (IS) is filled out by thick collagen (CL) bundles which form lattices represented by a network of capillaries. This network has the structure similar to a sponge porous matrix (SPM) with pores-capillaries of variable cross-section.
Keywords: interstitial space; interstitial fluids; fractal models